2015
DOI: 10.1016/j.geomorph.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Glacier change from the early Little Ice Age to 2005 in the Torngat Mountains, northern Labrador, Canada

Abstract: a b s t r a c tThe glaciers of the Torngat Mountains of northern Labrador are the southernmost of the Canadian Arctic and the easternmost of continental North America. Currently, 195 small mountain glaciers cover an area in excess of~24 km 2 , confined mostly to small cirques and upland depressions. Using a combination of field and remote sensing methods this study reconstructs and dates the areal extent of Torngat glaciers at their Neoglacial maximums, enabling the first assessment of regional glacier change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…In the spring, the distribution of the coldest and warmest portions of the landscape shifts to being more latitudinally controlled, with higher temperatures found along the Labrador Sea coastline relative to Hudson's Bay (Figure (b)). Elevation appears to control the air temperature distribution in summer, with the coldest portions of the landscape restricted to high elevations in northern Québec and in the Torngat Mountains of northern Labrador where small mountain glaciers still persist (Way et al , , ) (Figure (c)).The southeastern Labrador coastal region notably shifts from being the warmest region in the winter to one of the coldest regions in the summer, reflecting the coastal influences of the cold Labrador Current to the east and the Gulf of St Lawrence to the south. In the fall, the lowest air temperatures are present at similar locations as in the summer but include high elevations throughout the southern latitudes of the study area (Figure (d)).…”
Section: Resultsmentioning
confidence: 99%
“…In the spring, the distribution of the coldest and warmest portions of the landscape shifts to being more latitudinally controlled, with higher temperatures found along the Labrador Sea coastline relative to Hudson's Bay (Figure (b)). Elevation appears to control the air temperature distribution in summer, with the coldest portions of the landscape restricted to high elevations in northern Québec and in the Torngat Mountains of northern Labrador where small mountain glaciers still persist (Way et al , , ) (Figure (c)).The southeastern Labrador coastal region notably shifts from being the warmest region in the winter to one of the coldest regions in the summer, reflecting the coastal influences of the cold Labrador Current to the east and the Gulf of St Lawrence to the south. In the fall, the lowest air temperatures are present at similar locations as in the summer but include high elevations throughout the southern latitudes of the study area (Figure (d)).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, climate and reanalysis datasets are selected to view both 20th-century area changes and 1980s and late-2000s glacier mass balances in the context of prevailing climatic trends. This study builds on earlier work (Brown et al, 2012;Way et al, 2014;Way et al, 2015) and provides the first comprehensive, regional-scale remote-sensing and field-based assessment of the contemporary state of Labrador glaciers and their likely climate sensitivities, the results of which may be incorporated into both regional impact assessments and syntheses of global glacier mass balance.…”
Section: Introductionmentioning
confidence: 92%
“…Forbes, 1938;Henoch and Stanley, 1968), a complete inventory and analysis of the glaciers of the Torngat Mountains, covering a total active glacier area in 2005 of 22.5 ± 1.8 km 2 (not including relict ice), has only recently been completed and incorporated into global glacier datasets (Way et al, 2014;Pfeffer et al, 2014;Arendt et al, 2015). Combining the new regional glacier inventory (Way et al, 2014) with field-and remote-sensing-based analyses, Way et al (2015) showed a consistent glacial response to centennial-scale regional climate warming by documenting a 52.5 % reduction in ice extent since glaciers reached their Little Ice Age (LIA) maxima (dated to between 1581 and 1673).…”
Section: Introductionmentioning
confidence: 98%
“…The review team was composed of two members with graduatelevel permafrost science field experience in Labrador. One review team member (lead author) had completed five field seasons in the Torngat Mountains and completed regional remote sensingbased glacier and rock glacier inventories (e.g., Way et al 2014Way et al , 2015Way 2017). Prior to feature identification, each mapper was provided rock glacier identification training materials, video tutorials, and relevant publications.…”
Section: Study Areamentioning
confidence: 99%
“…In the Torngat Mountains of northern Labrador, modelling studies suggest that permafrost may be widespread (Way andLewkowicz 2016, 2018), but field observations of local permafrost conditions are lacking. Remote sensing and field-based glacier inventorying studies identified icecored moraines and rock glaciers at several locations within the boundary of Torngat Mountains National Park (Figure 1; Way et al, 2014Way et al, , 2015. A preliminary, unpublished rock glacier inventory created by a small team of mappers using SPOT5 satellite imagery identified 201 features in the region (Way 2017).…”
Section: Introductionmentioning
confidence: 99%